The dynamics of supply chain failure - Cox, Karsten (2018)
In today’s highly competitive global manufacturing industries, the reality facing most prime or focal manufacturing organisations around the world is one where resources have been reduced, inventory has been drained, technology spending curtailed, and processes that are not core to an organisation’s business have been scaled back and / or outsourced. In competitive global marketplaces prime manufacturers simply cannot afford to have any area of their operations compromised. Supply chain operations need to be robust and resilient in order to retain and increase market share. Supply chain failure is a phenomenon that can potentially cause major issues for many organisations, especially when failure becomes persistent. Supply chains may under-perform or fail in different ways. Here we are concerned with a particular kind of supply chain failure, persistent failure over time, which occurs when a supplier fails persistently to provide the level of quality and delivery performance originally expected or specified in an agreed contract. The phenomenon is observed in industries where there is a lack of substitute suppliers with adequate design and production capability and / or capacity, potentially high switching costs, and regulatory and accreditation issues. The goal of this research is to provide managers at prime manufacturing organisations with an effective way to understand their supply environment and provide insights to help identify and resolve supply problems that might otherwise become persistent failures. In this research project, we seek to understand and rationalize what persistent supply chain failure is, identify why it happens and what influences it. This is achieved by conducting new primary empirical research to examine the ‘mechanisms’ and ‘dynamics’ of persistent failure and how organisations react to persistent adversity in supply chains. Multiple case studies have been conducted in the Aerospace Industry to understand and explain the nature of the phenomenon of persistent failure. An analysis of the extensive empirical evidence collected has enabled a new model of persistent supply chain failure be developed using causal loop diagrams. The ‘Persistent Failure’ model helps to understand the causes of the phenomenon and helps to identify mitigating strategies that can limit its emergence in supply chain relationships. The empirical study, the qualitative and quantitative analyses, and the causal loop model of persistent failure provide a significant contribution to the body of knowledge in purchasing, supply chain and operations management.